Study of the compression behavior of functionally graded lattice for customized cranial remodeling orthosis. (June 2022) - Veloso, Fernando; Miranda, Daniel; Morais, Pedro; Torres, Helena R.; Oliveira, Bruno; Correia-Pinto, Jorge; Pinho, António C.M.; Vilaça, J.L.
Abstract: Deformational plagiocephaly is a head deformity that occurs in newborns, treated in severe cases with helmets named cranial remodeling orthoses (CRO). Current CROs can fail to adapt to head growth, causing excessive pressure sores and other complications, and may lead to poor clinical results. In this work, we experimentally and numerically study the compressive behavior of a functionally graded lattice that may be used in future work as a potential inner lining for a CRO with a customized density distribution. This work is divided into five stages. First, we describe the design of all lattices involved in the study. Second, we measure the mechanical properties of the bulk material used in the manufacturing of the lattices. Third, we study the effect of unit cell size variation, testing three homogenous body-centered cubic (BCC) lattices, and creating a numerical model for the prediction of the compressive behavior of various lattices with different unit cell sizes. Fourth, we study the effects of truss diameter variation, designing and testing three homogenous lattices with different truss diameters. Finally, we design a BCC lattice with a truss diameter gradient and analyze compressive deformations in numerical and experimental compression studies. The numerical simulations of the compression of the homogenous and graded lattices agree with the experimental measurements, both in unit cell variation and in truss diameter variation. In the graded lattice, the compression displacements observed in each region are proportional to their density and agree with the numerical simulation. Truss diameter variation was found to have a wider range of compressive responses than unit cell size variation without major changes in the overall geometry of the lattice and found more suitable for the intended application. The studies showed the potential of the functionally graded lattice for use in the CRO. Graphical abstract: Image 1 Highlights: A new concept for a FGAM lattice in cranial remodeling orthoses is proposed. Various lattices are studied numerically and experimentally for compression. Numerical models for the prediction of lattice compression behavior are presented. A proof-of-concept experiment for a tailored FGAM lattice is developed. The truss-based BCC FGAM lattice with a tailored compressive response is described.